Lead Concentration in The Blood of Smokers and Non-Smokers Workers in Car Repairing Shops in the City of Sebha, Libya - Saeda Maatoq,; Hajar Abu Ajila ,; Retaj Hussein , (AlQalam Journal of Medical and Applied Sciences, 2023)
Aim. This study aimed to estimate the element of lead in the blood serum of workers (smokers and non-smokers) in car repair shops in the city of Sebha, Libya. Methods. Blood samples were collected by a laboratory technician, and a questionnaire was prepared to collect specific data for each worker (age, weight, and duration of work). The sample size was (11) smoking workers and (37) non-smoking workers. About 3 replicates were taken for each sample. Lead was estimated using an atomic absorption device. One-way ANOVA with a confidence level of 95% (Levene's) and a t-test showed the correlation and difference between the concentration of lead in the workers' blood. Smokers and non-smokers. Results. There were significant differences at the level of P<0.05 for lead concentration between smokers and non-smokers. The smokers had an average of (20.8791±6.54131), and the non-smokers had an average of (12.8870±3.94090), and the value (f) of the Levene test calculated at a significance level (α=0.05) was (3.155), and the value (Sig) corresponding to the test. The (F) value was (0.082), the (T) value was (5.024), and the (sig) value corresponding to the (t) test was (0.000), which confirms the presence of statistically significant differences in lead concentration between smokers and non-smokers. The results of the statistical analysis showed to estimate lead concentration according to study variables (weight, age, years of work), there were significant differences in lead concentration according to body weight for smokers and non-smokers, while years of work. The results showed that there were no significant differences in lead concentration for smokers, while for non-smokers there were differences in Lead concentration according to years of work. While age, there are no significant differences in lead concentration for smoking workers. While for non-smokers there are significant differences. Conclusion. We conclude from this study that occupational exposure contributes significantly to increasing the concentration of lead in the blood, and this concentration increases with the presence of other sources of exposure, such as smoking. Years of work also contribute to the biological burden. So, for people exposed to lead.